Possibilities of correction of lipid-phospholipid disorders in patients with non-alcoholic steatohepatitis against obesity and pathology of the biliary tract. - A. Yu. Filippova (Medičnì Perspektivi)
High priority in the pathogenesis and treatment of non-alcoholic steatohepatitis (NASH) is given to disorders of lipid-phospholipid fractions, which are directly related to the functioning of hepatocytes. The aim of the study was to evaluate the effect of various complex treatment regimens on lipid-phospholipid fractions in patients with NASH in combination with obesity (OB) and pathology of the biliary tract (BT) according to a 6-month follow-up. 52 patients with NASH in combination with OB and BT pathology were examined. The control group consisted of 20 practically healthy individuals. The effect of complex treatment (preventive and therapeutic measures) on the indicators of lipid-phospholipid fractions in patients with NASH in combination with obesity and pathology of the biliary tract was studied. Changes in the indicators of serum lipid-phospholipid fractions were detected before treatment in all observation groups, which were accompanied by decrease in phospholipids (PL), phosphatidylcholine and sphingomyelin content and a significant increase in PL lysoforms – lysophosphatidylcholine and phosphatidylethanolamine, triglycerides, cholesterol esters (from p<0.05 to p<0.001). Combination therapy with the inclusion in the standard treatment of ursodeoxycholic acid and arginine glutamate in the comorbid course of NASH can be considered as a promising direction in the treatment of this category of patients, this allows to improve indicators of lipid-phospholipid fractions and stabilize the hepatocytes’ membrane (from p<0.05 to p<0.001).